Detectability comparison of simulated tumors in digital breast tomosynthesis using high-energy X-ray inline phase sensitive and commercial imaging systems. (March 2018) - Ghani, Muhammad U.; Wong, Molly D.; Omoumi, Farid H.; Zheng, Bin; Fajardo, Laurie L.; Yan, Aimin; Wu, Xizeng; Liu, Hong
Highlights: A high-energy X-ray phase sensitive and a commercial DBT systems were compared. A modular breast imaging phantom was used for the comparison purposes. Simulated tumor margins were better visualized for phase sensitive DBT imaging. Phase sensitive DBT showed an improvement in contrast and spatial resolutions. Superiority of phase sensitive DBT was endorsed by higher CNR and FOM values. Abstract: This study compared the detectability of simulated tumors using a high-energy X-ray inline phase sensitive digital breast tomosynthesis (DBT) prototype and a commercial attenuation-based DBT system. Each system imaged a 5-cm thick modular breast phantom with 50–50 adipose-glandular percentage density containing contrast-detail (CD) test objects to simulate different tumor sizes. A commercial DBT system acquired 15 projection views over 15 degrees (15d-15p) was used to acquire the attenuation-based projection views and to reconstruct the conventional DBT slices. Attenuation-based projection views were acquired at 32 kV, 46 mAs with a mean glandular dose (Dg ) of 1.6 mGy. For acquiring phase sensitive projection views, the prototype utilized two acquisition geometries: 11 projection views were acquired over 15 degrees (15d-11p), and 17 projection views were acquired over 16 degrees (16d-17p) at 120 kV, 5.27 mAs with 1.51 mGy under the magnification (M) of 2. A phase retrieval algorithm based on the phase-attenuation duality (PAD) was applied to each projection view, and a modified Feldkamp-Davis-Kress (FDK) algorithm was used to reconstruct the phase sensitive DBT slices. Simulated tumor margins were rated as more conspicuous and better visualized for both phase sensitive acquisition geometries versus conventional DBT imaging. The CD curves confirmed the improvement in both contrast and spatial resolutions with the phase sensitive DBT imaging. The superiority of the phase sensitive DBT imaging was further endorsed by higher contrast to noise ratio (CNR) and figure-of-merit (FOM) values. The CNR improvements provided by the phase sensitive DBT prototype were sufficient to offset the noise reduction provided by the attenuation-based DBT imaging.